A new training load quantification method at supramaximal intensity and its application in injuries among members of an international volleyball team - Bouzigues, T.; Maurelli, O.; Imbach, F.; Prioux, J.; Candau, R. (The Journal of Strength and Conditioning Research, 2024)
The quantification of training loads (TLs) is essential for optimizing jump performance and reducing the occurrence of injuries. This study aimed to (a) propose a new method for quantifying TLs in explosive exercises, (b) determine the nature of the relationship between TLs dynamics and injury occurrence, and (c) assess a TLcritical for training schedule purposes, above which the risk of injury occurrence becomes unacceptable. This study was conducted with 11 male volleyball players on a national team during a 5-month international competitive period. The proposed new method for quantifying TLs is based on a weighting factor applied to relative jumping intensities, determined by the number of sustainable jumps and their intensities measured by G-Vert accelerometer. The relationship between TLs dynamics and injury occurrence was assessed using a variable dose-response model. A high coefficient of determination was found between the maximum number of jumps possible and their intensities (r2 = 0.94 ± 0.14, p < 0.001), indicating a strong physiological relationship between jumping intensities and the constraints imposed. The occurrence of injury was dependent on TLs dynamics for 2 players (r2 = 0.26 ± 0.01; p < 0.001). The TLcritical corresponded to 11 jumps over 80% of maximum jump height during games and approximately 130 jumps at <80% of maximal jump height. The present study proposes a new approach for quantifying supramaximal exercises and provides tools for training schedules and the prevention of volleyball injuries.